Functional adaptation of presynaptic chemokine receptors in EAE mouse central nervous system. Issue 11 (19th August 2014) - Di Prisco, Silvia; Merega, Elisa; Pittaluga, Anna
ABSTRACT In cortical synaptosomes of Experimental Autoimmune Encephalomyelitis (EAE) mice at the early stage of disease (13 days post immunization, d.p.i.), the Regulated upon Activation Normal T cell Expressed and Secreted (RANTES, CCL5)‐mediated control of [3H]D‐aspartate ([3H]D‐ASP) exocytosis elicited by a mild depolarizing stimulus (12 mM KCl) shifted from inhibition to facilitation. By using selective antagonists for the chemokine receptor (CCR) 1, 3, and 5 subtypes, we found that the pharmacological profile of the receptor(s) accounting for CCL5‐mediated effect was unaltered when compared to control. Inasmuch, CCR protein expression was unaltered. This studies was not extended at 21 d.p.i. since, at this stage, CCL5 failed to affect [3H]D‐ASP exocytosis. At 13 d.p.i., the expression of CCR proteins was largely conserved when compared to control. In spinal cord synaptosomes of EAE mice at 21 d.p.i., when presynaptic defects became evident, the [3H]D‐ASP exocytosis elicited by 15 mM KCl was significantly increased when compared to control and it was significantly potentiated by 1 nM CCL5. The antagonist pharmacological profile and the western blot analysis of the CCR proteins unveiled that the receptor repertoire involved was unmodified. Differently from controls, however, the CCR1 antagonist BX513 efficiently inhibited on its own [3H]D‐ASP exocytosis suggesting that this receptor could have adopted an active conformation. Altogether, our observations favor the use of CCR antagonists to the cure of neurological symptoms in patients suffering from demyelinating syndrome. Synapse 68:529–535, 2014. © 2014 Wiley Periodicals, Inc.